Exercise Prevents Cognitive Function Decline and Demyelination in the White Matter of APP/PS1 Transgenic AD Mice - Zhang, Lei; Chao, Feng-Lei; Luo, Yan-Min; Xiao, Qian; Jiang, Lin; Zhou, Chun-Ni; Zhang, Yi; Lv, Fu-Lin; He, Qi; Ma, Jing; Tang, Yong (Current Alzheimer Research, 2017)
Background: Whether exercise could delay the cognitive function decline and structural changes in Alzheimer's disease (AD) are not fully understood. Methods: 6-month-old male APP/PS1 double transgenic mice ran four months and then the effects of exercise on the cognitive function and the white matter of AD were investigated. Results: The mean escape latency of the excercised group was significantly shortened when compared to that of the sedentary group. The percentage of time in target quadrant and the target zone frequency of the exercised group were significantly increased when compared to the sedentary group. The white matter volume, the myelinated fiber volume and axon volume in the white matter of the exercised group were significantly increased when compared to the sedentary group. Conclusion: Exercise could improve the cognitive function in AD, and the effects of exercise on the white matter of AD might be one of the structural bases for the protective effect of exercise on the cognitive function of AD. The exercise-induced protection of the white matter in AD might be due to the fact that the exercise prevented the demyelination of the myelinated fibers in the white matter of AD.
Keywords: stereology